Effects of two different recovery postures during high-intensity interval training - Michaelson, J. V.; Brilla, L. R.; Suprak, D. N.; McLaughlin, W. L.; Dahlquist, D. T. (Translational Journal of the American College of Sports Medicine, 2019)
The purpose of this study was to examine the effects of two different recovery postures, hands on head (HH) and hands on knees (HK), as a form of immediate recovery from high-intensity interval training (HIIT). Twenty female Division II varsity soccer players (age = 20.3 ± 1.1 yr, body mass index = 22.4 ± 1.80 kg·m -2 ) completed two experimental trials in a randomized, counterbalanced order. Each trial consisted of four intervals on a motorized treadmill consisting of 4 min of running (4 × 4) at 90%-95% HR max with 3 min of passive recovery between each interval. HR recovery was collected during the first 60 s of each recovery, where volume of carbon dioxide (V[Combining Dot Above]CO 2 ) and tidal volume (V T ) were recorded each minute during the 3-min recovery period. Results showed an improved HR recovery ( P < 0.001), greater V T ( P = 0.008), and increased V[Combining Dot Above]CO 2 ( P = 0.049), with HK (53 ± 10.9 bpm; 1.44 ± 0.2 L·min -1 , 1.13 ± 0.2 L·min -1 ) compared with HH (31 ± 11.3 bpm; 1.34 ± 0.2 L·min -1 , 1.03 ± 0.2 L·min -1 ). These data indicate that HK posture may be more beneficial than the advocated HH posture as a form of immediate recovery from high-intensity interval training.